Identification of pigments related to allergic tattoo reactions in 104 human skin biopsies - Serup, Jørgen (Contact Dermatitis, 2019)
BACKGROUND: Red tattoos are prone to allergic reactions. The identity of the allergen(s) is mostly unknown. OBJECTIVES: Chemical analysis of human skin biopsies from chronic allergic reactions in red tattoos to identify culprit pigment(s) and metals. MATERIAL AND METHODS: One hundred four dermatome biopsies were analyzed by matrix‐assisted laser desorption/ionization tandem mass spectrometry (MALDI‐MS/MS) for identification of commonly used organic pigments. Metal concentrations were assessed by inductively coupled plasma (ICP)‐MS and x‐ray fluorescence (XRF). Fourteen patients had cross‐reactions in other red tattoos. RESULTS: In total, the identified pigments were mainly azo Pigment Red (P.R.) 22 (35%), P.R. 210 (24%), P.R. 170 (12%), P.R. 5 (0.9%), P.R. 112 (0.9%), and Pigment Orange (P.O.) 13 (11%). P.R. 122 (0.9%) and Pigment Violet (P.V.) 23 (8%) were also common. P.R. 22, P.R. 170, and P.R. 210 also dominated in patients with cross‐reactions. In 22% of the biopsies, no red pigment was detected. Element analysis indicated the presence of the sensitizers nickel and chromium. CONCLUSIONS: P.R. 22, P.R. 170, and P.R. 210 were identified as the prevailing pigments behind chronic allergic reactions in red tattoos. The epitope causing the reaction might be a pigment‐degradation product. Metal contamination may derive from different sources, and its role in red tattoo allergy cannot be ascertained.